Visi Meningkatkan dan Memeratakan Mutu Pendidikan: Quo Vadis Transformasi Sekolah? - Siti Reni; Masduki Asbari; Mohamad Biazt Ramadhan (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to see the quality of improving the quality of education in Indonesia with the educational Transformation program. In this study report, a descriptive qualitative method is used by taking notes because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's Youtube Channel entitled "Siniar #PojokDikbud "School Transformation to Improve and Equalize the Quality of Education" explained by the host named Dea Rizkita and the resource person, namely the Director General of PAUD, Primary Education and Secondary Education, namely Mr. Jumeri. The results of this study explain that the School Transformation Program is a program to improve the quality of education, one of which is encouraging the transformation process of educational units so that it can improve student learning outcomes and improve the quality of teaching and learning activities in schools. This program provides benefits for schools, including improving the quality of education, ensuring equal distribution of the quality of education with a program to increase the capacity of school principals in order to achieve quality learning.